A PRELIMINARY STUDY ON THE POSSIBLE ASSOCIATION BETWEEN DENTAL ANXIETY AND DIGESTIVE MANIFESTATIONS IN HEALTHY JAPANESE INDIVIDUALS - Iulia Antioch; Ovidiu-Dumitru Ilie; Alin Ciobica; Norina Forna; Furuta Tsumugu; Kawahara Ichiro; Mihoko Tomida (Romanian Society of Oral Rehabilitation, 2023)
Background: As highlighted in ROME IV, irritable bowel syndrome (IBS) is a multifactorial psychosocial disorder marked by the presence of several changes in intestinal transit. Not only is difficult for patients to perform daily practice but for health professional as well since there is still uncertainty regarding the measurement of these symptoms and effect of prescribed treatment. Material and methods: This is why the present study aimed to assess the incidence of gastrointestinal symptoms through the VAS-IBS questionnaire in healthy Japanese individuals. To establish if there is causation, we also applied a dental anxiety form. Results: Following the allocation of both VAS-IBS and dental anxiety questionnaires, we observed that there are no statistically significant differences between sexes in terms of anxiety perceived regarding dental procedures (p >0.05). On the other hand, we noted that males are more prone to physical symptoms than women, especially abdominal pain and diarrhoea (p <0.05; Tukey HSD and Bonferroni for "abdominal pain" (p = 0.0229) and "diarrhoea" (p = 0.0181). Conclusions: In this way, the present study brings additional evidence regarding the usefulness of these questionnaires in human patients regardless of their health status.